Локализация и современное состояние Левобережного Цимлянского городища – Саркел (Белая Вежа) - Ткаченко, Ю.Г.; Хохлов, С.А.; Горлов, И.О.; Горлов, И.О.; Садеков, Р.Н.; Фазлуллин, С.М. (Хазарский альманах, 2020)
In May 2019, the flooded in 1952 Left-bank Tsimlyanskaya Fortress – Sarkel (Belaya Vezha) was localized. The discovery was made using sonar readings and the subsequent diving search. The data obtained were compared with maps of the fortess and reports of 19th and 20th century archaeologists concerning Sarkel’s research and coincided with high accuracy. The current state of Sarkel allows him to continue his archaeological research. In addition, it can become a kind of testing ground for testing modern remote geophysical research methods.